Immunometabolism of Phagocytes During Mycobacterium tuberculosis Infection - Kumar, Ranjeet; Singh, Pooja; Kolloli, Afsal; Shi, Lanbo; Bushkin, Yuri; Tyagi, Sanjay; Subbian, Selvakumar (Frontiers in Molecular Biosciences, 2019)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb) remains as a leading killer among infectious diseases worldwide. The nature of the host immune response dictates whether the initial Mtb infection is cleared or progresses towards active disease, and is ultimately determined by intricate host-pathogen interactions that are yet to be fully understood. The early immune response to infection is mediated by innate immune cells, including macrophages and neutrophils that can phagocytose Mtb and mount an antimicrobial response. However, Mtb can exploit these innate immune cells for its survival and dissemination. Recently, it has become clear that the immune response and metabolic remodeling are interconnected, which is highlighted by the rapid evolution of the interdisciplinary field of immunometabolism. It has been proposed that the net outcome to Mtb infection – clearance or chronic disease - is likely a result of combined immunologic and metabolic activities of the immune cells. Indeed, host cells activated by Mtb infection have strikingly different metabolic requirements than naïve/non-infected cells. Macrophages activated by Mtb-derived molecules or upon phagocytosis acquire a phenotype similar to M1 with elevated production of pro-inflammatory molecules and rely on glycolysis and pentose phosphate pathway to meet their bioenergetic and metabolic requirements. In these macrophages, oxidative phosphorylation and fatty acid oxidation are dampened. However, the non-infected/naive, M2-type macrophages are anti-inflammatory and derive their energy from oxidative phosphorylation and fatty acid oxidation. Similar metabolic adaptations also occur in other phagocytes, including dendritic cells, neutrophils upon Mtb infection. This metabolic reprogramming of innate immune cells during Mtb infection can differentially regulate their effector functions, such as the production of cytokines and chemokines, and antimicrobial response, all of which can ultimately determine the outcome of Mtb-host interactions within the granulomas. In this review, we describe key immune cells bolstering host innate response and discuss the metabolic reprogramming in these phagocytes during Mtb infection. We focused on the major phagocytes, including macrophages, dendritic cells and neutrophils and the key regulators involved in metabolic reprogramming, such as hypoxia-inducible factor-1, mammalian target of rapamycin, the cellular myelocytomatosis, peroxisome proliferator-activator receptors, sirtuins, arginases, inducible nitric acid synthase and sphingolipids.